Species That Fly at a Higher Game: Patterns of Deep–Water Emergence Along the Chilean Coast, Including a Global Review of the Phenomenon - Häussermann, Vreni; Ballyram, Stacy Anushka; Försterra, Günter; Cornejo, Claudio; Ibáñez, Christian M.; Sellanes, Javier; Thomasberger, Aris; Espinoza, Juan Pablo; Beaujot, Francine (Frontiers in Marine Science, 2021)
Deep-water emergence (DWE) is the phenomenon where marine species normally found at great depths (i.e., below 200 m), can be found locally occurring in significantly shallower depths (i.e., euphotic zone, usually shallower than 50 m). Although this phenomenon has been previously mentioned and deep-water emergent species have been described from the fjord regions of North America, Scandinavia, and New Zealand, local or global hypotheses to explain this phenomenon have rarely been tested. This publication includes the first literature review on DWE. Our knowledge of distribution patterns of Chilean marine invertebrates is still very scarce, especially from habitats below SCUBA diving depth. In our databases, we have been gathering occurrence data of more than 1000 invertebrate species along the Chilean coast, both from our research and from the literature. We also distributed a list of 50 common and easily in situ-identifiable species among biologically experienced sport divers along the Chilean coast and recorded their sighting reports. Among other findings, the analysis of the data revealed patterns from 28 species and six genera with similar longitudinal and bathymetric distribution along the entire Chilean coast: along the Chilean coast these species are typically restricted to deep water (>200 m) but only in some parts of Chilean Patagonia (>39°S–56°S), the same species are also common to locally abundant at diving depths (<30 m). We found 28 of these ‘deep’ species present in shallow-water of North Patagonia, 32 in Central Patagonia and 12 in South Patagonia. The species belong to the phyla Cnidaria (six species), Mollusca (four species), Arthropoda (two species) and Echinodermata (16 species). We ran several analyses comparing depth distribution between biogeographic regions (two-way ANOVA) and comparing abiotic parameters of shallow and deep sites to search for correlations of distribution with environmental variables (Generalized Linear Models). For the analyses, we used a total of 3328 presence points and 10635 absence points. The results of the statistical analysis of the parameters used, however, did not reveal conclusive results. We summarize cases from other fjord regions and discuss hypotheses of DWE from the literature for Chilean Patagonia.